Primary Erythrocytosis in a Bitch - Clinical and Laboratorial Aspects - Dalla Porta Eder, Vanessa; Loeff Zardo, Izadora; Quishpe Contreras, Laura Victoria; Faria Valle, Stella (Acta Scientiae Veterinariae, 2022)
Background: Primary erythrocytosis is a rare myeloproliferative disorder in dogs and cats characterized by an autonomous proliferation of erythroid precursors in the bone marrow, with low to normal serum erythropoietin concentration, resulting in elevated red blood cell count, hematocrit and hemoglobin concentration. Clinical signs are associated with increased blood volume and viscosity, and may include erythema, hyperemic mucous membranes and neurological signs such as seizures and ataxia. In veterinary medicine, the diagnosis should be made by exclusion of secondary or relative causes, after complementary exams. This report aims to describe a case of primary erythrocytosis in a bitch. Case: A 4-year-old mixed-breed bitch was referred to the Veterinary Medical Teaching Hospital of the UFRGS with 3 convulsive episodes related by the owner. A previous abdominal ultrasonography revealed splenomegaly and the electrocardiogram showed no abnormalities. No alterations were observed at the physical examination. The laboratorial blood tests demonstrated a persistent erythrocytosis, with high hematocrit, hemoglobin and red blood cells count, thrombocytopenia and neutropenia, and total plasmatic protein was within the reference interval. The bone marrow cytology revealed reduced cellularity, normal myeloid:erythroid ratio, erythroid hyperplasia, mild myeloid hyperplasia and moderate myelofibrosis. The serum erythropoietin measurement was within the reference range, and the blood gas analysis detected a slight decrease in partial oxygen pressure. Therefore, no evidence of secondary conditions was observed and the diagnosis of primary erythrocytosis could be made. Discussion: Since there is no definitive method, the diagnosis of primary erythrocytosis could be based on the exclusion of all secondary and relative causes of erythrocytosis. The absence of clinical signs of dehydration and high serum albumin levels were findings that conduced for the exclusion of the relative form of the disturbance. The echocardiography and the abdominal ultrasonography ruled out any cardiopulmonary condition or kidney neoplasm, the most common causes of absolute secondary erythrocytosis. The persistently high hematocrit levels and red blood cell counts are significant for the suspicion of primary erythrocytosis, although thrombocytopenia and neutropenia are not commonly reported. The clinical signs of seizure were correlated with increased blood viscosity and reduced blood flow at the central nervous system. The blood gas analysis discarded the occurrence of systemic hypoxia, and the normal levels of erythropoietin gives higher evidence of the occurrence of an autonomous proliferation of the erythroid precursors within the bone marrow. The bone marrow cytology confirmed erythroid hyperplasia and the reduced cellularity that could be attributed to myelofibrosis. Myelofibrosis was described in humans with polycythemia vera, but there are no reports in veterinary, and this occurrence must be elucidated. An identical mutation in the JAK2 gene was observed in humans with polycythemia vera and dogs with primary erythrocytosis, and occurs in more than 50% of humans with myelofibrosis. Further investigations are necessary for veterinary medicine. In conclusion, the systematic approach of all organic systems and the assessment of complementary exams are necessary for the diagnostic of primary erythrocytosis in dogs. This condition should be considered in the differential diagnosis of any erythrocytosis, considering the guarded prognosis of this hematologic disorder. Keywords: myeloproliferative disorders, erythropoietin, myelofibrosis